(untitled) (The Pretoria Student Law Review, 2021)
As observed by Coetzee and Roestoff, the South African natural person insolvency system remains creditor oriented and as a ramification many over-indebted consumers are excluded from access to debt alleviation measures.1 There are three debt alleviation measures available to natural persons in South Africa, of which only the sequestration procedure under the Insolvency Act provides an over-indebted consumer with a discharge from pre-insolvency debts.2 However, the principal requirement of proving financial advantage to creditors restricts access for many debtors as they do not have sufficient disposable assets to satisfy the requirement.3 The other two debt alleviation measures are the administration order provided in the Magistrates Court4 and debt review under section 86 of the National Credit Act.5 These measures have been heavily criticised for their reliance on the courts and for only providing debt repayment plans with no provision for discharge.6 This article commences with a detailed discussion of the debt intervention procedure provided by the 2019 National Credit Amendment Act.7 Thereafter, the New Zealand insolvency system is discussed. The purpose is to benchmark the debt intervention procedure against the New Zealand insolvency system in order to ascertain if it obliterates a creditor-oriented approach.